A Large Skull Defect Due to Gorham-Stout Disease: Case Report and Literature Review on Pathogenesis, Diagnosis, and Treatment - de Keyser, Catherine E.; Saltzherr, Michael S.; Bos, Eelke M.; Zillikens, M. Carola (Frontiers in Endocrinology, 2020)
A 24-year old man was referred to the Erasmus MC Bone Center because of an asymptomatic increasing skull defect of the left parietal bone. The defect was first noticed at the age of six, and gradually increased over the years. His medical history was unremarkable, without any known trauma and a negative family history for bone diseases. Laboratory tests showed a low vitamin D level without other abnormalities. Particularly, there was no increase in markers of inflammation or bone turnover. CT-scans of the skull showed an osteolytic region of the parietal skull bone, with a two-centimeter increase in diameter over nine years. Contrast enhanced MRI showed lymphangiogenic invasion, which was compatible with our suspicion of Gorham-Stout disease. The patient was referred to the neurosurgeon for treatment with a bone graft while considering additional drug treatment. Gorham-Stout or vanishing bone disease is a rare entity characterized by progressive osteolysis with lymphangiogenic bone invasion. Although already reported in 1838, currently the diagnosis and treatment of Gorham-Stout disease is still challenging. The underlying pathophysiology is not clarified yet and several theories exist. The disease usually affects persons younger than 40 years and the majority present with bone disease of the maxillofacial region, the upper extremities or the torso. The clinical presentation includes most frequently pain, swelling and functional impairment of the affected region, but the disease can also be asymptomatic. Laboratory investigations are usually normal, and diagnosis is based upon imaging and sometimes pathology examination of affected bone tissue. Treatment is experimental and there is no general consensus about the best option due to lack of randomized controlled trials. Case reports showed patients treated with bisphosphonates, interferon-alpha, anti-VEGF therapy, mTOR inhibitors, and radiotherapy. There are some reports of surgery with prosthetic or bone grafts but no long-term follow-up data exist. This paper describes a unique case of Gorham-Stout disease of the parietal skull bone and discusses the current state of knowledge about this rare bone disease.